2018
DOI: 10.1007/s40843-018-9238-6
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages loaded CpG and GNR-PEI for combination of tumor photothermal therapy and immunotherapy

Abstract: Nano-therapeutic approach for clinical implementation of tumors remains a longstanding challenge in the medical field. The main challenges are rapid clearance, offtarget effect and the limited role in the treatment of metastatic tumors. Toward this objective, a cell-mediated strategy by transporting photothermal reagents and CpG adjuvant within macrophage vehicles is performed. The photothermal reagents are constructed by conjugating of hyperbranched polyethyleimine (PEI) to golden nanorode (GNR) via S-Au bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 36 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…In addition to biomechanical factors, biochemical factors and nonmalignant cells, such as CAFs, immune cells, and endothelial cells in tumor microenvironment, can all affect therapeutic responses [16][17][18]. CAFs constitute a majority of the structural scaffold of solid tumors and play a critical role in tumor survival and progression via secretion of various growth factors, cytokines, and chemokines and degradation of extracellular matrix proteins [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biomechanical factors, biochemical factors and nonmalignant cells, such as CAFs, immune cells, and endothelial cells in tumor microenvironment, can all affect therapeutic responses [16][17][18]. CAFs constitute a majority of the structural scaffold of solid tumors and play a critical role in tumor survival and progression via secretion of various growth factors, cytokines, and chemokines and degradation of extracellular matrix proteins [19].…”
Section: Introductionmentioning
confidence: 99%
“…The combination therapy in cancer treatment achieved rapid development in both research and clinical practice [1,2]. As we all know, due to the poor permeability of cytotoxic drugs in solid tumors, more and more attention has been paid to the combination therapy consisting of vascular disrupting agents (VDAs) [3,4], which can block the nutrients and oxygen supply by destroying the tumor vessels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the antigens released by dead tumor cells and the CpG adjuvant activated the body's antitumor immune response and ultimately effectively inhibited the growth of the tumor. [120] In another study, it was found that macrophages significantly improved the tumor-targeted delivery of NPs. The system ((WO+ICG)@ PLGA NP-loaded macrophages) significantly suppressed the tumor through immunotherapy and PTT in the B16 subcutaneous tumor model.…”
Section: Innate Immune-cell-based Antitumor Immunotherapeuticsmentioning
confidence: 98%
“…Macrophages are living cell carriers that use endocytosis to engulf anticancer drugs and deliver them and have strong drug tolerance and innate phagocytotic capabilities. [120] Chen and coworkers prepared macrophages loaded with the immune adjuvant CpG and gold nanorod (GNR)-polyethylenimine (PEI). Macrophages loaded with GNR-PEI/CpG obviously promoted drug accumulation in the tumor and significantly enhanced the effect of photothermal tumor therapy.…”
Section: Innate Immune-cell-based Antitumor Immunotherapeuticsmentioning
confidence: 99%